IMPLEMENTASI MANAJEMEN KEPALA SEKOLAH DALAM PENINGKATAN KINERJA GURU - Ai Qurotul Ain , (UNISAN JURNAL, 2024)
The purpose of this study is to explain the principal's leadership strategy in improving teacher performance at SD Islam Miftahul Ulum , mentioning the obstacles to the principal's leadership strategy in improving teacher performance at SD Islam Miftahul Ulum . describes how to overcome the constraints of the principal's leadership strategy in improving teacher performance at SD Islam Miftahul Ulum . The literature review used to analyze the results of this study, namely the Principal's Strategy and Leadership and Teacher Performance and the Principal's Strategy in Improving teacher performance. The method used in this research is descriptive-analysis using a qualitative approach, data collection techniques with the stages of observation, interviews and documentation. The research procedure is planning, collecting data, describing, analyzing and concluding. The results of the study, the principal's leadership strategy in improving teacher performance at SD Islam Miftahul Ulum by increasing discipline, providing motivation, being an example for teachers and education staff and conducting supervision. Constraints that occur in the principal's leadership strategy in improving teacher performance at SD Islam Miftahul Ulum , some teachers are late for school, leave earlier than the time specified in ending the school teaching and learning process, are not motivated in improving performance, do not respond to the example of leadership and supervision in SD Islam Miftahul Ulum Performances are held only once a year, lack of school infrastructure, supervisors have less role in coaching. The principal way to overcome obstacles in improving teacher performance at SD Islam Miftahul Ulum is to improve discipline, provide motivation in developing human resources, the principal supervises once a quarter and coordinates with related parties to complete learning infrastructure.